2005
DOI: 10.1017/s1431927605050257
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Structure of the Lingual Papillae of the Common Opossum (Didelphis marsupialis)

Abstract: The mammalian tongue has evolved for specialized functions in different species. The structure of its papillae tells about the animal's diet, habit, and taxonomy. The opossum has four kinds of lingual papillae (filiform, conical, fungiform, vallate). Scanning electron microscopy of the external features, connective tissue cores, and corrosion casts of the microvasculature show the filiform papillae have a spearhead-like main process and spiny accessory processes around the apical part of the main process. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
24
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 23 publications
9
24
0
2
Order By: Relevance
“…The vallate papillae in the present study were observed on the root region of the tongue, as is reported in other mammals (Qayyu et al, 1988;Pastor et al, 2008). Only two vallate papillae were observed in the distal third of Bradypus variegatus' tongue, corroborating with the results from Benetti et al (2009) in Bradypus torquatus and agreeing with what was observed in other Xenarthras, such as armadillos (Morais and Watanabe, 1988;Morais et al, 1994;Estecondo et al, 2001;Estecondo et al, 2004;Ciuccio et al, 2008).…”
Section: The Ventral Face Of the Bradypus Variegatus'supporting
confidence: 90%
See 3 more Smart Citations
“…The vallate papillae in the present study were observed on the root region of the tongue, as is reported in other mammals (Qayyu et al, 1988;Pastor et al, 2008). Only two vallate papillae were observed in the distal third of Bradypus variegatus' tongue, corroborating with the results from Benetti et al (2009) in Bradypus torquatus and agreeing with what was observed in other Xenarthras, such as armadillos (Morais and Watanabe, 1988;Morais et al, 1994;Estecondo et al, 2001;Estecondo et al, 2004;Ciuccio et al, 2008).…”
Section: The Ventral Face Of the Bradypus Variegatus'supporting
confidence: 90%
“…The morphology of the tongue of the animals can suffer variations according to the taxonomy, habitat, behavior and diet (Okada and Schraufnagel, 2005). According to findings by Jackowiak and Godynicki (2004), the presence, distribution and structure of the taste buds are correlated to the feeding habits of the animal, and it can vary and suffer adaptations (Pastor et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In puma, the dorsal surface of the lingual apex and body was entirely covered by filiform papillae that was reported in many carnivorous species such as bear (Pastor et al, 2011), jaguar (Emura, Okumura & Chen, 2013), ferret (Takemura et al, 2009), opossum (Okada & Schraufnagel, 2005) and fishing cat (Emura & Okumura, 2014). In the present study, filiform papillae had many secondary projections that emerged from the base of main papillae.…”
Section: Discussionsupporting
confidence: 77%